Perbedaan Hasil Belajar Sejarah dengan Menggunakan Model Pembelajaran Student Facilitator and Explaining dan Mind Mapping Kelas X Di SMA Plus Bina Satria Rupit - Getsah Afriweni; Ira Miyarni; Sarkowi Sarkowi (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2021)
This study aims to determine the differences in the results of learning history using the Student Facilitator And Explaining and Mind Mapping Class X learning model at SMA Plus Bina Satria Rupit. The research method used in this study was a quasi-experimental with random sampling method. The average result of the pre-test in the experimental class I was 55.18 and in the experimental class II was 54.3. while the post-test average value in the experimental class I after being given post-test treatment using the Student Facilitator And Expalinning model was 81.32, and in the experimental class II given Mind Mapping learning was 76.53. Based on the results of data analysis using the average difference test (Paired sample T test) obtained the final test value in sig. (2-Tiled) = 0.00 < 0.05, then Ho is rejected, Ha is accepted. Thus, it can be concluded that there are differences in the results of learning history using the Student Facilitator And Explaining and Mind Mapping Class X learning model at SMA Plus Bina Satria Rupit.